Evaluation of three different glassy composites (quinary matrix designed using Cr2O3/Na2O/MnO2) in respect of radiation shielding behaviors - Toker, Ozan; Bilmez, Bayram; Toker, Melis O.; Kavanoz, H. Birtan; Akcali, Ozgur; Yilmaz, Mehmet; Icelli, Orhan (TAYLOR & FRANCIS LTD, 2021)
Novel multiple glassy composite materials were offered for gamma shielding applications, photovoltaic applications, nuclear engineering, etc. as an alternative to concrete and pure lead. Studied glassy composite materials demonstrated better gamma-ray shielding than ordinary glass and concrete in the 15 keV-15 MeV energy range. The multiple composites were prepared with (xA + 0.11B + 0.02C + (0.87 - x)[(1 - y)D1 + yD2] = 1) recipe. BXCOM software was used to calculate exposure buildup factors (EBFs), energy absorption buildup factors (EABFs), and effective atomic numbers (Z(eff)). Monte Carlo simulations were performed via MCNP 6.2 code to evaluate the important shielding factors like mass attenuation coefficients (mu(m)), half-value layers (HVLs) and compared with XCOM results. The quinary composites were compared in each step with each other to determine which component is better for radiation shielding [(Cr2O3/Na2O/MnO2), Sb2O3, B2O3, V2O5, and Fe2O3]. From the investigated ratios, Cr2O3 and MnO2 at 85%, and Na2O at 70% were evaluated to be the best ratios to reduce radiation dose in the incident energy range. Also, Fe2O3 addition at 10% enhanced shielding ability. According to the simulation results, the quinary MnO2 composite (MnO2/Sb2O3/B2O3/V2O5/Fe2O3) was determined to have the best shielding property among all the studied composites. A gamma spectroscopy system with NaI(Tl) detector was used to determine the shielding properties of this best material, experimentally. All the studied composites indicate better gamma shielding properties than concrete, some of them are approaching pure lead.
Keywords: Buildup factors; Cr2O3; MnO2; Na2O; Monte Carlo simulation; radiation shielding; OPTICAL-PROPERTIES; OXIDE; COMPUTATION; Nuclear Science & Technology; Physics